Predicting bioavailability of monoclonal antibodies after subcutaneous administration: Open innovation challenge - Manuel Sánchez-Félix; Matt Burke; Hunter H. Chen; Claire Patterson; Sachin Mittal (2020)
Despite the increasing trend towards subcutaneous delivery of monoclonal antibodies, factors influencing the subcutaneous bioavailability of these molecules remain poorly understood. To address critical knowledge gaps and issues during development of subcutaneous dosage forms for monoclonal antibodies, the Subcutaneous Drug Delivery and Development Consortium was convened in 2018 as a pre-competitive collaboration of recognized industry experts. One of the Consortium's eight problem statements highlights the challenges of predicting human bioavailability of subcutaneously administered monoclonal antibodies due to a lack of reliable in vitro and preclinical in vivo predictive models. In this paper, we assess the current landscape in subcutaneous bioavailability prediction for monoclonal antibodies and discuss the gaps and opportunities associated with bioavailability models for biotherapeutics. We also issue an open challenge to industry and academia, encouraging the development of reliable models to enable subcutaneous bioavailability prediction of therapeutic large molecules in humans and improve translation from preclinical species.